Analysis of quarter-car 2 degree-of-freedom semiactive systems - Ihsan, Sany Izan; Faris, Waleed Fekry; Ahmadian, Mehdi (2007)
Several control policies of quarter-car 2 degree-of-freedom semiactive system, namely skyhook, groundhook and hybrid controls are presented. Their ride comfort, suspension displacement and road-holding performances are analyzed and compared with passive system. The analysis covers both transient and steady state responses in time domain and transfer function in frequency domain. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the uspension displacement for typical passenger cars. The hybrid control policy is also shown to be a bettercompromise between comfort, road-holding and suspension displacement than the skyhook and groundhook control policies.